IMPLEMENTASI CANVA DAN QUIZIZZ DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK DIGITAL GURU SMP - Saripuddin; Melissa Puspita; Anin Asnidar; Saati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This community service activity aims to describe the implementation process and analyze the impact of workshops on the use of Canva visual media and Quizizz digital quizzes in enhancing the digital pedagogical competence of junior high school teachers at UPT SMPN 1 and 2 Galesong Selatan. The main problem faced by teachers is the dominance of conventional teaching methods and the low utilization of digital media. The evaluation results showed an average teacher satisfaction score of 4.4 out of 5.0 (very high category). The activity successfully improved teachers’ ability to design engaging and interactive learning media. These findings are consistent with studies by Patto dkk. (2025) and Dewi & Febriyanti (2025), which indicate that the use of Canva and Quizizz effectively increases student engagement and teachers’ digital literacy.